Electron-hole asymmetry in the phase diagram of carrier-tuned CsV3Sb5 - Capa Salinas, Andrea N.; Ortiz, Brenden R.; Bales, Calvin; Frassineti, Jonathan; Mitrović, Vesna F.; Wilson, Stephen D. (Frontiers in Electronic Materials, 2023)
Here we study the effect of electron doping the kagome superconductor CsV3Sb5. Single crystals and powders of CsV3Sb5−xTex are synthesized and characterized via magnetic susceptibility, nuclear quadrupole resonance, and x-ray diffraction measurements, where we observe a slight suppression of the charge density wave transition temperature and superconducting temperature with the introduction of electron dopants. In contrast to hole-doping, both transitions survive relatively unperturbed up to the solubility limit of Te within the lattice. A comparison is presented between the electronic phase diagrams of electron-and hole-tuned CsV3Sb5.